A fully-aqueous red-fluorescent probe for selective optical sensing of Hg2+ and its application in living cells. (July 2016) - Pola, Murali Krishna; Ramakrishnam Raju, Mandapati V.; Lin, Chein-Ming; Putikam, Raghunath; Lin, Ming-Chang; Epperla, Chandra Prakash; Chang, Huan-Cheng; Chen, San-Yuan; Lin, Hong-Cheu
Abstract: A new red-fluorescent mercury ion sensor material is designed and synthesized, which is composed of a tweezer-shaped hydrophilic probe containing bifurcated soft-base atoms N and S coupled with 2-dicyanomethylene-3-cyano-4, 5, 5-trimethyl-2, 5-dihydrofuran (TCF) unit. By virtue of the strong electron-accepting nature of TCF unit (as a push–pull chromophore), this designed sensor material can selectively detect Hg 2+ over various tested metal ions in a 100% aqueous medium via naked-eye and photoluminescence (PL) observations. Theoretical and time-resolved photoluminescence measurements further confirmed the selectivity and reversibility of the probe towards Hg 2+ via intramolocular charge transfer mechanism in this sensor material. Moreover, the living cell tests by confocal fluorescence images of this sensor material towards Hg 2+ were also investigated. Finally, distinguished absorption changes and fluorescence quenching spectral appearances allowed us to present the selective optical indicator of Hg 2+ via TCF moiety for the first time. Graphical abstract: Highlights: A water soluble and reversible Hg 2+ ion sensor probe is synthesized. This probe works as a colorimetric and naked-eye sensor towards Hg 2+ ion. A large blue shift is observed in absorption of the probe coordinated with Hg 2+ . This probe has the optical sensor potential to be used in living cell applications.